2021
DOI: 10.1177/1545968321989353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Robotic Therapy Associated With Noninvasive Brain Stimulation on Upper-Limb Rehabilitation After Stroke: Systematic Review and Meta-analysis of Randomized Clinical Trials

Abstract: Background Robot-assisted therapy and noninvasive brain stimulation (NIBS) are promising strategies for stroke rehabilitation. Objective This systematic review and meta-analysis aims to evaluate the evidence of NIBS as an add-on intervention to robotic therapy in order to improve outcomes of upper-limb motor impairment or activity in individuals with stroke. Methods This study was performed according to the PRISMA Protocol and was previously registered on the PROSPERO Platform (CRD42017054563). Seven databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
1
23
0
1
Order By: Relevance
“…These include early reperfusion therapies (i.e., intravenous thrombolysis and mechanical thrombectomy) aimed at limiting damage and preventing further cell death to contain lesion size and disability [ 1 ]. Furthermore, traditional (neurofacilitation or functional retraining through either shaping or task practice) and advanced rehabilitation protocols, including pharmacological manipulation to increase sprouting and anatomical plasticity, non-invasive brain stimulation (NIBS) to modulate the activity of targeted brain areas, and robot-aided rehabilitation (RAR) to perform an intensive, repetitive, assisted-as-needed, and task-oriented motor practice, are available in any phase of the post-stroke recovery process [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. These rehabilitation strategies aim to increase the adaptive plasticity processes (mainly experience-dependent plasticity mechanisms) that develop in lesional and perilesional tissues [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include early reperfusion therapies (i.e., intravenous thrombolysis and mechanical thrombectomy) aimed at limiting damage and preventing further cell death to contain lesion size and disability [ 1 ]. Furthermore, traditional (neurofacilitation or functional retraining through either shaping or task practice) and advanced rehabilitation protocols, including pharmacological manipulation to increase sprouting and anatomical plasticity, non-invasive brain stimulation (NIBS) to modulate the activity of targeted brain areas, and robot-aided rehabilitation (RAR) to perform an intensive, repetitive, assisted-as-needed, and task-oriented motor practice, are available in any phase of the post-stroke recovery process [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. These rehabilitation strategies aim to increase the adaptive plasticity processes (mainly experience-dependent plasticity mechanisms) that develop in lesional and perilesional tissues [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent meta-analysis showed that NIBS combined with other therapies was effective in improving upper extremity motor function and activities of daily living in acute/subacute stroke patients, but not in chronic stroke patients ( 28 ). In contrast, a meta-analysis by Reis et al ( 29 ) indicated that there were not enough data about the benefits of NIBS as an additional intervention to robotic-assisted therapy on upper extremity motor function or activity in stroke patients. Therefore, to the best of our knowledge, this study is the first meta-analysis summarizing the findings on MT combined with NIBS in upper limb motor function recovery after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Literatürde noninvaziv beyin stimülasyon (NIBS) tedavilerinin tıbbi rehabilitasyon uygulamalarına ilave edilmesinin üst ekstremite fonksiyonel gelişimini artırdığına dair birçok klinik çalışma yer almaktadır. [3][4][5][6][7][8][9][10][11][12] NIBS uygulamaları ile lezyonlu hemisferdeki motor korteksin uyarılabilirliğini artırmak ya da kontralezyonel hemisferde aşırı uyarılabilirliği azaltmak ve inmeli hastalarda interhemisferik dengenin tekrar kurulmasına yardımcı olmak hedeflenmektedir. NIBS uygulamaları içerisinde yer alan repetetif transkraniyal manyetik stimülasyon (rTMS), transkraniyal doğru akım stimülasyonu (TDAS), transkraniyal alternatif akım stimülasyonu gibi farklı stimülasyon prosedürlerinin birbirlerine üstünlüğünü gösteren çalışma bulunmamaktadır.…”
Section: Abstract Objectiveunclassified